Isolated penile Fournier’s: a caveat - Rajendran, Theakarajan; Paneerselvam, Rajapriyan; Verma, Shikhar; Gopal, Balasubramanian (International Surgery Journal, 2021)
Isolated penile Fournier’s gangrene is a rare condition causing significant morbidity to the patients. It occurs due to urinary tract infection or trauma. We describe an elderly male who presented with blackish discoloration of the skin of the penis with fever. Examination revealed a necrotic patch over the shaft of the penis without any other foci of infection around the perineum. Penis was debrided, and the antibiogram showed Escherichia coli sensitive to amikacin. He received seven days of antibiotics, and the wound granulated well. A split skin graft was used to cover the wound to prevent contraction. This unusual presentation requires expeditious management to prevent mortality and morbidity.